RELIGIOUS ACTIVITIES AND PANCASILA STUDENT PROFILE IN STRENGTHENING CHARACTER EDUCATION - Luthfi Adnan; Nurul Fadlilah; Ahmad Jauhar Fuad (LP2M IAI Al-Khairat Pamekasan, 2026)
The Pancasila Student Profile, initiated by the Indonesian Ministry of Education and Culture, aims to shape students who are not only intellectually capable but also spiritually and morally grounded. One of the core elements of this profile is developing faith in God Almighty, religious devotion, and noble character. In the face of increasing challenges in education, teacher creativity plays a vital role in fostering effective, inspiring, and meaningful learning experiences. This study, entitled